2009
DOI: 10.3329/jsr.v2i1.2643
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> and <i>In Vivo</i> Antioxidant Potential of Hydromethanolic Extract of <i>Phoenix dactylifera</i> Fruits

Abstract: The present study was aimed at investigating the antioxidant activities of the hydromethanolic extract of Phoenix dactylifera (HEPD) fruit (Arecaceae). The antioxidant activities of extract have been evaluated by using a range of in vitro assays and in vivo hepatoprotective model. In case of in vitro studies the IC50 values were found to be 160, 1400, 1115, 1050 μg/ml in DPPH, nitric oxide, superoxide, hydroxyl radical scavenging assays, respectively. In case of in vivo studies the levels of liver enzymatic, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 10 publications
1
60
0
1
Order By: Relevance
“…Besides it also exhibits free radical scavenging properties by either through scavenging or chelating process (Usmani, 2013, Ebrahimzadeh et al, 2008, Roy et al, 2013. Flavonoids are large class of benzo-pyrone derivatives, ubiquitous in plants exhibit antioxidant activity (Naskar et al, 2010). Total flavonoid content is expressed as μg of quercetin equivalents (QE)/mg of extract.…”
Section: Estimation Of Total Flavonoid Contentmentioning
confidence: 99%
“…Besides it also exhibits free radical scavenging properties by either through scavenging or chelating process (Usmani, 2013, Ebrahimzadeh et al, 2008, Roy et al, 2013. Flavonoids are large class of benzo-pyrone derivatives, ubiquitous in plants exhibit antioxidant activity (Naskar et al, 2010). Total flavonoid content is expressed as μg of quercetin equivalents (QE)/mg of extract.…”
Section: Estimation Of Total Flavonoid Contentmentioning
confidence: 99%
“…Phenolic compounds like flavonoïds and tannins are good antioxidant substances which have been reported to have biological activities and prevent or control oxidative stress related disorders. 39 The crude extract tested negative to alkaloids.This finding is contrary to report of Conserva and Ferreira et al in 2012 that alkaloids were present in species of Borreria. 40 Previous studies indicated that many phenolic and steroidal compounds possessed anti-plasmodial activities.…”
Section: Discussionmentioning
confidence: 99%
“…Phoenix dactylifera is famous for its use in treating jaundice and in women before and after delivery in traditional medicine practice. Naskar et al (2010) reported that water-methanolic extract of date fruit possesses potent antioxidant effect and free radical scavenging activity in addition to its hepatoprotective effect. Date syrup can replace honey by 75% because of their similarity in sugar content.…”
Section: Hepatoprotectionmentioning
confidence: 99%
“…A hydromethanolic extract of P. dactylifera fruit showed high antioxidant activity, reducing power, free radical scavenging activity, the antioxidant potential was attributed to phytoconstituents (flavonoids, saponins, tannins, steroids) and vitamin C (Naskar et al, 2010). Furthermore, aqueous P. dactylifera extract was found to inhibit significantly the lipid peroxidation, protein oxidation and also exhibited a potent superoxide and hydroxyl radical scavenging activity in a dose dependent manner in vitro (Vyawahare et al, 2008).…”
Section: Introductionmentioning
confidence: 99%